Bridging the Digital Divide for Older Adults: An Investigation of Barriers and Facilitators - Head, Milena; Hassanein, Khaled (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
As Information and Communication Technologies (ICT) become increasingly pervasive, older adults often face significant barriers to digital inclusion. This research-in-progress paper investigates the multi-faceted barriers and facilitators affecting ICT use and embracement among older adults. Barriers include cognitive decline, physical limitations, lack of digital skills, and psychosocial factors such as low confidence and distrust. Facilitators encompass inclusive interface design and motivational support tailored to older adults' needs. The study employs a mixed-methods approach, combining behavioral surveys, interviews, and neurophysiological measures to capture comprehensive insights into older adults' ICT experiences. By involving older adults in the co-design of ICT interfaces and identifying effective motivational strategies, this research aims to develop empirically driven tools and guidelines to enhance digital inclusion and well-being for older adults, ultimately bridging the digital divide.